An easy way of solving this is solving for t on the x=t^2+2t equation and putting into the other equation y=2t

you have to solve it by completing the square on x=t^2+2t

so after doing that, you get x+1=(t+1)^2

then square root both sides +√(x+1)=t+1 and -√(x+1)=t+1

then -1 to both sides t=-1+√(x+1) and t=-1-√(x+1)

substitute both of those into the equation y=2t

and you get y=2(-1+√(x+1)) and y=2(-1-√(x+1))

simplified, you get y=-2+2√(x+1) and y=-2-2√(x+1)

you get two equations because when you graph the parametric equation, you get a sideways parabola, therefore, it is not a function, and has to be split into two different functions so it is possible to be graphed.